Utilizing Public Relations Communication Strategies to Enhance Community Partnership in Saudi Educational Health Institutions. (The International Journal of Educational Sciences and Arts, 2025)
This study aimed to explore the effectiveness of employing public relations communication strategies in enhancing community partnership within Saudi educational health institutions, with a field application on Al-Moosa College for Health Sciences. The study adopted the media survey methodology by conducting structured interviews accompanied by a questionnaire with several employees from the Public Relations and Marketing Department, as well as individuals involved in community initiatives within the college. The study sample consisted of public relations specialists who were deliberately selected due to their direct relevance to the research topic, which contributed to providing rich data and a comprehensive analysis covering various dimensions of the studied phenomenon.The results revealed a clear effectiveness in using public relations communication strategies and activities to enhance community partnership within Al-Moosa College. The findings also indicated that public relations significantly contribute to building a positive institutional image. Additionally, the results showed that the institution effectively utilizes social media platforms to strengthen its engagement with the local community and implements various forms of community partnerships, including awareness initiatives, health programs, and interactions with students and their families. The study also confirmed the presence of clear communication plans adopted by the college's Public Relations Department to support the sustainability of community partnership and enhance the institution’s social impact. In light of these findings, the study recommends the need to promote the adoption of dialogic and interactive strategies in institutional communication to ensure the active involvement of the local community in the planning, implementation, and evaluation of health and educational programs.
Keywords: Communication Strategies; Public Relations; Community Partnership; Educational Health Institutions; Institutional Communication; Contingency Model; Digital Platforms